Body size variations in caribou ecotypes and relationships with demography - Couturier, Serge; Otto, Robert D.; Côté, Steeve D.; Luther, Glenn; Mahoney, Shane P. (Journal of Wildlife Management, 2020)
In many vertebrates size is one of the most influential and variable individual characteristics and a strong determinant of reproductive success. Body size is generally density dependent and decreases when intraspecific competition increases. Frequent and long‐distance movements increase energy expenditures and, therefore, may also influence body size, particularly in highly mobile species. Caribou (Rangifer tarandus, also known as reindeer) exhibit tremendous variation in size and movements and thus represent an excellent candidate species to test the relationships between body size, population size, and movements. We analyzed body measurements of adult female caribou from 7 herds of the Québec‐Labrador Peninsula, Canada, and we related their morphology to population size, movements, and annual ranges. The herds represented 3 ecotypes (migratory, montane, and sedentary). Ecotypes and herds differed in size (length), shape (roundness), and movements. The sedentary ecotype was larger and moved 4 to 7 times less than the migratory ecotype in the 1990s. At the start of a demographic growth period in the early 1960s, migratory caribou from the Rivière‐George (hereafter George) herd had longer mandibles than caribou of the sedentary ecotype. Mandible length in the George herd declined in the 1980s after rapid population growth, while individuals performed extensive movements and the herd's annual range increased. Migratory caribou then became shorter than sedentary caribou. After the George herd decline in the 1990s, mandible length increased again near levels of the 1980s. Caribou from the migratory Rivière‐aux‐Feuilles herd later showed a similar decline in mandible length during a period of population growth, associated with longer movements and increasing annual range. We hypothesize that the density‐dependent effect observed on body size might have been exerted through summer habitat degradation and movement variations during herd growth. Our study has 2 important implications for caribou management: the ...